Assessment of the Knowledge of General Dentists Practicing in Tehran about Timing of Orthodontic Treatment - Arzani, Vida; Ghasemi, Hadi; Tehranchi, Azita (Journal of Dental School, 2019)
Objective: The ideal time to commence orthodontic treatment is very important. In Iran, due to the widely distributed population and low number and uneven distribution of orthodontists, general dental practitioners (GDPs) play an important role in proper treatment of occlusal and functional disorders and referring orthodontic patients to orthodontists. The purpose of this study was to assess the knowledge of GDPs about the proper timing of orthodontic treatment in comparison with orthodontists practicing in Tehran. Methods: This cross-sectional analytical study was conducted on GDPs and orthodontists practicing in Tehran, who were selected by random sampling. The questionnaire used in this survey asked for demographic information including age, sex, academic degree, work place and work experience and contained questions concerning the knowledge of clinicians regarding the proper time to commence treatment for the most common types of occlusal disorders, functional disorders, temporomandibular joint (TMJ) disorders and other orthodontic problems. The answers of both groups of participants were assessed based on the American Board of Orthodontics objective grading system (ABO OGS). Results: The results of ANOVA showed that the two groups were significantly different in terms of age (p<0.05), sex, academic degree (p<0.001), and place of work (private office, private clinic, governmental clinic) (p<0.05). The results of comparison of GDPs and orthodontists for the proper time of initiation of orthodontic treatment for occlusal, functional and TMJ disorders showed that the GDPs had significantly less knowledge in this regard. Conclusion: Because of low level of knowledge of GDPs about the ideal time to commence orthodontic treatment, further training regarding diagnosis of malocclusion in primary and mixed dentition periods, etiology of malocclusion, recognition of normal occlusion and normal dental relationships as well as the proper time to start orthodontic treatment for each type of disorder seems necessary